Manu’s Vision of the Hindu Dharma - Manickam, T. M. (Journal of Dharma, 1975)
The socio-religious life of the Aryan people seems to have achieved a cultural maturity at the stage of the formation of the Dharma-Laws as promulgated by Manu, probably a mythical figure to whom the "Dharma-Laws" are attributed. The Hindus who claim cultural lineage to the Aryan stalk of civilization respect Manusmrti as their book of the "Rules of conduct" with respect to their socio-moral and religious life. The Manusmrti presents in a systematic form the laws of Hindu Dharma. The Hindu Dharma is essentially a way of life to be lived following strict moral principles in view of realizing a great religious ideal, moksha, which is strongly founded on a philosophy of life.